Chronic Antibiotic Dependent Pouchitis Is Associated With Older Age at the Time of Ileal Pouch Anal Anastomosis (J-pouch) Surgery. Issue 3 (26th September 2019) - Weaver, Kimberly N; Kochar, Bharati; Hansen, Jonathan J; Isaacs, Kim L; Jain, Animesh; Sheikh, Shehzad Z; Fichera, Alessandro; Chaumont, Nicole; Sadiq, Tim; Koruda, Mark; Long, Millie D; Herfarth, Hans H; et al.
Abstract: Background: Risk factors for the development of chronic antibiotic dependent pouchitis (CADP) are not well understood. Methods: Using multivariable logistic regression, we compared clinical factors between 194 patients with acute antibiotic responsive pouchitis or CADP. Results: Individuals with CADP were significantly older (40.9 vs 30.8 years, P < 0.001) and demonstrated a longer disease duration before IPAA (10.3 vs 7.0 years, P = 0.004). Age ≥55 years at the time of IPAA was significantly associated with CADP (adjusted odds ratio = 4.35, 95% confidence interval = 1.01–18.7). Conclusions: Although older age should not represent a barrier to IPAA, further studies evaluating etiologies of this association are warranted. Lay Summary: In this study of patients with ulcerative colitis who underwent a colectomy with ileal pouch-anal anastomosis, patients age 55 years and older at the time of surgery had an increased risk of developing chronic antibiotic dependent pouchitis.